A SEIR model with memory effects for the propagation of Ebola-like infections and its dynamically consistent approximation. (September 2021) - Iqbal, Zafar; Macías-Díaz, J.E.; Ahmed, Nauman; Aziz-ur Rehman, M.; Raza, Ali; Rafiq, Muhammad
Highlights: An epidemic model with memory that describes the propagation of Ebola-type diseases is presented. The reproductive number, the equilibria and their stability are rigorously discussed. A computer method to solve the system with memory is proposed and theoretically analyzed. The simulations confirm that the method preserves many features of the analytical solutions. Abstract: Background and objective. We present and analyze a nonstandard numerical method to solve an epidemic model with memory that describes the propagation of Ebola-type diseases. The epidemiological system contemplates the presence of sub-populations of susceptible, exposed, infected and recovered individuals, along with nonlinear interactions between the members of those sub-populations. The system possesses disease-free and endemic equilibrium points, whose stability is studied rigorously. Methods. To solve the epidemic model with memory, a nonstandard approach based on Grünwald–Letnikov differences is used to discretize the problem. The discretization is conveniently carried out in order to produce a fully explicit and non-singular scheme. The discrete problem is thus well defined for any set of non-negative initial conditions. Results. The existence and uniqueness of the solutions of the discrete problem for non-negative initial data is thoroughly proved. Moreover, the positivity and the boundedness of the approximations is also theoretically elucidated. Some simulations confirm the validity of these theoretical results. Moreover, the simulations prove that the computational model is capable of preserving the equilibria of the system (both the disease-free and the endemic equilibria) as well as the stability of those points. Conclusions. Both theoretical and numerical results establish that the computational method proposed in this work is capable of preserving distinctive features of an epidemiological model with memory for the propagation of Ebola-type diseases. Among the main characteristics of the numerical integrator, the existence and the uniqueness of solutions, the preservation of both positivity and boundedness, the preservation of the equilibrium points and their stabilities as well as the easiness to implement it computationally are the most important features of the approach proposed in this manuscript.